Cracked tooth syndrome - Maria Tanumihardja (Journal of Dentomaxillofacial Science, 2009)
Cracked tooth syndrome is usually found in daily dental practice. The incidence ofcracks teeth tends to increasing. People are living longer and keeping their teethlonger. As a consequence, people have more complex restoration and endodontictreatment, leaving teeth more prone to cracks. In addition, stressful lives may provokeunconscious habits such as clenching and bruxism which can induce cracks in teeth.However, many cracks teeth can be saved nowadays when the characteristic signsand symptoms of cracked tooth syndrome can be diagnosed earlier in itsdevelopment